Comparison of the Efficacy of Fosfomycin Trometamol and Ciprofloxacin in Transrectal Ultrasound-Assisted Prostate Biopsy Prophylaxis: Clinical Results of A Tertiary Referral Center - Mehmet Hamza Guktekin; Goktug Kalender; Kadir Can Sahin; Sami Berk Ozden; Ilker Inanc Balkan; Muhammed Fatih Simsekoglu; Bulent Onal; Ahmet Erozenci (Haseki Tıp Bülteni, 2023)

(untitled)
Aim:Although infectious complications after a prostate biopsy are uncommon, they may have fatal outcomes. An efficient prophylaxis plan has not been defined in the current literature to reduce these problems. In this study, we aimed to compare the use of ciprofloxacin (CIP) and fosfomycin trometamol (FT) for prophylaxis in terms of infectious complications and morbidity-related parameters in patients who underwent transrectal ultrasound-guided prostate biopsy (TRUSPB).Methods:The study included 104 patients who received FT for TRUSPB prophylaxis (group 1) between May 2021 and May 2022 and 113 patients who received CIP for TRUSPB prophylaxis between April 2020 and April 2021 (group 2). All patients were instructed to visit our hospital if they had any complaints relevant to the procedure, and outpatient control visits were scheduled one month after the procedure. Post-procedure infectious or non-infectious complications within one month were identified by screening the patients’ electronic records and medical charts belonging to their inpatient, outpatient, or emergency department visits.Results:After the biopsy procedures, the rates of lower urinary tract symptom development, positive urine cultures, and the requirement of hospitalization for parenteral antibiotic treatment were found to be significantly lower in group 1 than in group 2 (p=0.048). In the analyses performed independently of the prophylaxis regimen, it was observed that an increase in the Charlson Comorbidity Index of the patients caused a significant increase in the rates of both urosepsis (p=0.024) and the requirement of hospitalization for parenteral antibiotic treatment (p<0.001).Conclusion:We observed that the use of FT for prophylaxis in TRUSPB was superior to the use of CIP in terms of reducing infectious complications.